EUS-BD for calibration of benign stenosis of the bile duct in patients with altered anatomy or inaccessible papilla - Caillol, Fabrice; Godat, Sébastien; Solovyev, Alexey; Harouchi, Amina; Oumrani, Sarra; Marx, Mariola; Hoibian, Solene; Dahel, Yanis; Ratone, Jean-Philippe; Giovannini, Marc (Endoscopy International Open, 2024)
Background and study aims In cases of inaccessible papilla, EUS-guided biliary drainage (EUS-BD) has been described as an alternative to calibrate benign biliary stenosis. However, few studies are available.Patients and methods This tw-center, retrospective study was designed to evaluate technical success and clinical success at 1 year. All patients who underswent EUS-BD without the rendezvous technique used for calibration of benign biliary stenosis were included from 2016 to 2022. Patients underwent EUS-hepaticogastrostomy (EUS-HGS) during the first session. Then, HGS was used to access the bile duct, allowing calibration of the stenosis: Dilation of the biliary stenosis and placement of double pigtail stents through the stenosis for 1 year.Results Thirty-six patients were included. Technical success was 89% (32/36), with four failures to cross the stenosis but EUS-HGS was performed in 100% of the cases. Nine patients were excluded during calibration because of oncological relapse in six and complex stenosis in three. Three patients had not yet reached 1 year of follow-up. Twenty patients had a calibration for at least 1 year. Clinical success after stent placement was considered in all cases after 1 year of follow-up. Thirteen patients underwent stent removal and no relapse occurred after 435 days of follow-up (SD=568). Global morbidity was 41.7% (15/36) with only one serious complication (needing intensive care), including seven cases of cholangitis due to intrabiliary duct obstruction and five stent migrations. No deaths were reported.Conclusions EUS-BD for calibration in case of benign biliary stenosis is an option. Dedicated materials are needed to decrease morbidity.
Keywords: Pancreatobiliary (ERCP/PTCD); Strictures; Biliary tract; Endoscopic ultrasonography; Intervention EUS